Microwave‐Assisted Rapid Synthesis of Graphene‐Supported Single Atomic Metals. Issue 35 (17th July 2018) - Fei, Huilong; Dong, Juncai; Wan, Chengzhang; Zhao, Zipeng; Xu, Xiang; Lin, Zhaoyang; Wang, Yiliu; Liu, Haotian; Zang, Ketao; Luo, Jun; Zhao, Shenglong; Hu, Wei; et al.
Abstract: Graphene‐supported single atomic metals (G‐SAMs) have recently attracted considerable research interest for their intriguing catalytic, electronic, and magnetic properties. The development of effective synthetic methodologies toward G‐SAMs with monodispersed metal atoms is vital for exploring their fundamental properties and potential applications. A convenient, rapid, and general strategy to synthesize a series of monodispersed atomic transition metals (for example, Co, Ni, Cu) embedded in nitrogen‐doped graphene by two‐second microwave (MW) heating the mixture of amine‐functionalized graphene oxide and metal salts is reported here. The MW heating is able to simultaneously induce the reduction of graphene oxide, the doping of nitrogen, and the incorporation of metal atoms into the graphene lattices in one simple step. The rapid MW process minimizes metal diffusion and aggregation to ensure exclusive single metal atom dispersion in graphene lattices. Electrochemical studies demonstrate that graphene‐supported Co atoms can function as highly active electrocatalysts toward the hydrogen evolution reaction. This MW‐assisted method provides a rapid and efficient avenue to supported metal atoms for wide ranges of applications. Abstract : Microwave (MW) heating is used for the rapid preparation of graphene‐supported single atomic metals. With MW heating, graphene oxide reduction, nitrogen doping, and metal incorporation are achieved in a single two‐second process, minimizing metal atom diffusion to achieve exclusive atomic dispersion. This offers a facile approach to wide ranges of single atomic metals with intriguing catalytic, magnetic and electronic properties.